Hsp90 in the continuum of breast ductal carcinogenesis: Evaluation in precursors, preinvasive and ductal carcinoma lesions - Zagouri, Flora (BioMed Central, 2010)
BACKGROUND: Hsp90 (heat shock protein90) is a chaperone protein essential for preserving and regulating the function of various cellular proteins. Elevated Hsp90 expression seems to be a trait of breast cancer and may be an integral part of the coping mechanisms that cancer cells exhibit vis-à-vis stress. This manuscript tries to examine the immunohistochemical expression of Hsp90 all along the continuum of breast ductal lesions encompassing ductal hyperplasia without atypia (DHWithoutA), atypical ductal hyperplasia (ADH), ductal carcinoma in situ (DCIS) and invasive ductal carcinoma (IDC). METHODS: Tissue specimens were taken from 30 patients with DHWithoutA, 31 patients with ADH, 51 with DCIS and 51 with IDC. Immunohistochemical assessment of Hsp90 was performed both in the lesion and the adjacent normal breast ducts and lobules; the latter serving as control. Concerning Hsp90 assessment the percentage of positive cells and the intensity were separately analyzed. Subsequently, the Allred score was calculated. Post hoc analysis on the correlations between Hsp90 Allred score and possible predictors (grade, nodal status, tumor size, ER Allred score, PR Allred score, c-erbB-2 status and triple negative status) was conducted in IDC. RESULTS: Hsp90 exhibited mainly cytoplasmic immunoreactivity. Hsp90 Allred score exhibited an increasing trend along the continuum of breast ductal lesions (Spearman's rho = 0.169, p = 0.031). Compared to the adjacent normal ducts and lobules, no statistically significant differences were noted in DHwithoutA, ADH and DCIS. Hsp90 expression (intensity, positive cells, Allred score) was higher in IDC, compared to the adjacent normal tissue. Higher Hsp90 expression was observed in grade 2/3 IDCs (borderline association) and tumors of larger size. At the univariable analysis, higher Hsp90 expression was associated with higher ER Allred score, PR Allred score and c-erbB-2 positivity in IDC. Triple-negative IDCs exhibited significantly lower Hsp90 expression. The multivariable logistic regression model revealed that between the three markers, solely ER Allred score and c-erbB-2 positivity were independently associated with higher Hsp90 expression in IDC. CONCLUSION: The above point to significant variability in Hsp90 expression with significant implications upon the effectiveness and limitations of anti-Hsp90 drugs.